Fluid and electrolyte balance in children. Issue 11 (November 2017) - Terris, Mark; Crean, Peter
Abstract: Safe intravenous fluid prescription in children requires an understanding of certain basic principles to avoid adverse events. Careful consideration needs to be given to both the appropriate rate and composition of the fluids to be administered with frequent re-assessment. In this review we examine the indications for parenteral fluid management; specifically maintenance fluid requirements, correction of any fluid deficit and replacement of ongoing losses. The role of non-osmotic secretion of anti-diuretic hormone (ADH) is discussed and children at particular risk are identified. We review complications associated with intravenous fluid therapy, in particular hyponatraemic encephalopathy and discuss the management of this medical emergency. Other electrolyte abnormalities that may arise are highlighted. Fluid management in children with diabetic ketoacidosis is also reviewed.